2018
DOI: 10.1016/s2095-3119(17)61784-2
|View full text |Cite
|
Sign up to set email alerts
|

The damage risk evaluation of Aphis gossypii on wheat by host shift and fitness comparison in wheat and cotton

Abstract: Aphids are considered as one of the key pests for wheat production worldwide. Major aphid species that infest wheat in China include Sitobion avenae, Rhopalosiphum padi, Schizaphis graminum and Metopolophium dirhodum. However, during our wheat field survey in Wenshang County of Shangdong Province, China, we observed that Aphis gossypii can feed on wheat. The damage risk of A. gossypii on wheat was assessed using host shift method. A population of A. gossypii collected from a wheat field in 2015 and another pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Mody et al (2007) demonstrated that host plant shifting had a strong effect on Chrysopsyche imparilis (Lepidoptera: Lasiocampidae), especially in adult fecundity and the mean body mass of second-instar larvae [9]. Furthermore, when assessing the effects of host plant shifting based on the life table and population dynamics of Aphis gossypii (Glover) (Hemiptera: Aphididae), Fan et al (2018) showed that the fecundity (F), intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rate (R 0 ) significantly increased when transferred from wheat to cotton [10]. Amarasekare et al (2008) reported the survival rates of P. marginatus on different host plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Mody et al (2007) demonstrated that host plant shifting had a strong effect on Chrysopsyche imparilis (Lepidoptera: Lasiocampidae), especially in adult fecundity and the mean body mass of second-instar larvae [9]. Furthermore, when assessing the effects of host plant shifting based on the life table and population dynamics of Aphis gossypii (Glover) (Hemiptera: Aphididae), Fan et al (2018) showed that the fecundity (F), intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rate (R 0 ) significantly increased when transferred from wheat to cotton [10]. Amarasekare et al (2008) reported the survival rates of P. marginatus on different host plants [11].…”
Section: Introductionmentioning
confidence: 99%